PEMBUATAN BIODIESEL DARI MINYAK KELAPA MELALUI PROSES TRANS-ESTERIFIKASI - Pardi, Pardi; Satriananda, Satriananda (Jurnal Sains dan Teknologi Reaksi, 2008)
Ethyl ester and gliserol produce by reacting coconut oil with ethanol. Ethyl ester also called biodiesel, because it has a close characteristic with diesel oil. The source of biodiesel come from natural plants that contain oil. This research used trans-esterification method to produce biodiesel from coconut oil. Reaction held by varying temperatur at 60oC, 70oC and 80 oC and mol ratio of coconut oil to ethanol varying from 1 : 3, 1 : 5 to 1 : 7. The result shows the range of kinematic viscosity laying between 1,498 – 1,650 cm2/s, density range 0,809 – 0,812 gr/cm3 and flash point range 78 – 79 oC. Maximum yield 64 % ethyl ester reach at mol ratio coconut oil to ethanol 1: 7 and reaction temperature 70oC.Key words : biodiesel, trans-esterification reaction, coconut oil and ethyl ester.